The struggle of being Toba in contemporary Argentina: Processes of ethnic identification of indigenous children in contexts of language shift - Hecht, Ana Carolina (2012)
The aim of this article is to study how children experience their ethnic identifications in relation to their knowledge of the Toba language through daily interactions with peers and adults (both indigenous and non-indigenous). The study is focused on an urban setting in Buenos Aires (Argentina) where monolingual (Spanish) practices are replacing bilingual ones (Spanish-Toba), and where the Toba language is a valuable feature of ethnicity. From an anthropological perspective, this article focuses on the identity constructions of the children. Finally, it re-examines the agency of the children and looks at how their life experiences impact on their contextual identities.